Politicizing place perception: a phenomenology of urban activism in Istanbul. (1st October 2015) - Houston, Christopher
Abstract : Phenomenology intuits that people's perception of the environment is related to their lived activities, emotions, and perspectives, and is in this process also temporally experienced. This article applies these insights to political activism, exploring its conditioning of militants' sensory experience of the city and showing how militants' urban knowledge is intimately connected to political practices of organizing, mobilizing, and agitating, each orientated in turn by the pursuit of revolution. Based on fieldwork in Istanbul with ex‐militants and their memories of political action from the years immediately before and after the 1980 military coup, the article applies and extends phenomenological understandings of place perception to explore their changing experiences of the city. This quality of perception as a temporal process is vital for understanding both historical and contemporary features of ex‐militants' remembering of Istanbul, related as they are to a state project to shape and simplify public knowledge of their activities, and to certain political developments posited by activists themselves as efficacious in transforming the meaning of their past acts. It concludes by illustrating how these two processes come together in the recent institution by ex‐militants of a new museum (12 September Museum of Shame), opened some thirty years after the events it objectivizes.